Robust surface reconstruction of teeth from raw pointsets. (5th December 2013) - Mao, Zhihong; Park, Kyusic; Lee, Kunwoo; Li, Xiongbing
SUMMARY This paper discusses a 3D robust dental surface reconstruction method. The surface reconstruction method usually consists of the following stages: mesh generation, surface registration, and surface merging. A large amount of noise will be accumulated after these three processes especially for the dental model with many sharp features of high curvature. To obtain an accurate dental surface, this paper first strengthens the mesh generation and the surface registration using optimal parameters. Then, a 3D robust dental surface reconstruction is performed by iteratively executing the smallest univalue segment assimilating nucleus filtering method and the surface attraction method. Finally, virtual scanning and real scanning models are introduced to validate the accuracy of the presented method. The experiments show that our method can robustly reconstruct the 3D dental model. Copyright © 2013 John Wiley & Sons, Ltd.